Slope stability analysis at Pit AI-Block B PT. Anugerah Alam Andalas Muara Ketalo Village, Sungai Bengkal, Tebo Ilir Subdistrict, Tebo District, Jambi Province - Dasri Husien; Bambang Heriyadi; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2018)
Slope stability was not currently analysed into mining production at company. Bishop Simplified and Janbu Simplified will be applied to the slopes.Data bases are Top Soil: Unit Wight (γ)= 20,36 kN/m3, Cohesion (c') =26,38 kN/m2 and angle of repose (ϕ') = 25,5°.Sands: Unit Wight (γ) = 22,19 kN/m3, Cohesion (c') = 28,14 kN/m2 and angle of repose (ϕ') = 33,3°. Clay: Unit Wight (γ) =19,67 kN/m3, Cohesion (c') = 32,16 kN/m2 and angle of repose (ϕ') = 39,11°. Initial Slope height 22 metre and overall slope angles are 46°, Single Slope height I 5 metreand slope angle 48°, Single Slope Height II 17 metre and slope angle 55°.Geometrical slope recommendations are: 1. Bishop Simplified Method SF 0,892, slope is not safe. Reducing slope angle (46° to 30°) increasing II single slope to III single slope and height 6,115, 8,885, 7 metre, angels 30°,39°, 56°, berm I 4,221 metre berm II 4,601 metre, SF is now 1,338, slope is safe. 2. Janbu Simplified Method (saturated) SF 0,784, slope is not safe. Reducing slope angle (46° to 30°) and increasing II single slope to III single slope and height 6,115, 8,885, 7 metre, then angle 28°,32°, 56°, berm I 2,689 metre and berm II 4,601 meter, SF is1,337 and slope is safe.